Pembuktian Tindak Pidana Pencucian Uang Hasil Tindak Pidana Korupsi Pengadaan Barang/Jasa Di Kota Madiun - Puti Dwi Jayanti; Tofik Yanuar Chandra; Yuhelson Yuhelson; Ramlani Lina Sinaulan; Madeline Vanessa Audrey (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
Procurement of goods/services is still a source of corruption cases in Indonesia and ensnare many Regional Heads, so the increasing number of criminal acts of corruption in the procurement of goods/services will greatly affect the growth and development of money laundering crimes which are used as a means for perpetrators to secure the proceeds. crime from law enforcement. How is the application of criminal sanctions against perpetrators of money laundering as a result of corruption, and evidence of criminal acts of procurement of goods/services in the City of Madiun. The aim of this study is to analyze and understand the application of criminal sanctions to perpetrators of money laundering resulting from corruption in the procurement of goods/services, as well as proving the crime of money laundering resulting from corruption in the procurement of goods/services in Madiun City. This research has theoretical and practical uses. The research method uses a normative juridical approach, namely an approach that focuses on studies of the science of law and its principles that apply in society and then describes existing phenomena and analyzes them systematically. The theory used is the theory of proof and the theory of punishment. From the results of the study it was found that the application of sanctions against the perpetrators of money laundering and corruption in the procurement of goods/services in the City of Madiun was subject to a limited cumulation system (het gematigde cumulatie stelsel), because it was a concurrent action (concursus realis). For those who make it, they are subject to separate punishments in accordance with the crimes they have committed, but the amount may not be heavier than the maximum maximum sentence plus one third. The legal basis for concurrent acts (concursus realis) is Article 66 Paragraph 1 of the Criminal Code (KUHP). Proof of money laundering as a result of corruption in the procurement of goods and services in Madiun City uses the theory of proof or the proof system adopted in Indonesia, namely the negative system according to law (Negatief Wettelijk Stelsel).